Is the Occurrence of the Sticking Region in Maximum Smith Machine Squats the Result of Diminishing Potentiation and Co-Contraction of the Prime Movers among Recreationally Resistance Trained Males? - van den Tillaar, Roland (Int J Environ Res Public Health, 2021)
This study compared the kinetics, barbell, and joint kinematics and muscle activation patterns between a one-repetition maximum (1-RM) Smith machine squat and isometric squats performed at 10 different heights from the lowest barbell height. The aim was to investigate if force output is lowest in the sticking region, indicating that this is a poor biomechanical region. Twelve resistance trained males (age: 22 ± 5 years, mass: 83.5 ± 39 kg, height: 1.81 ± 0.20 m) were tested. A repeated two-way analysis of variance showed that Force output decreased in the sticking region for the 1-RM trial, while for the isometric trials, force output was lowest between 0–15 cm from the lowest barbell height, data that support the sticking region is a poor biomechanical region. Almost all muscles showed higher activity at 1-RM compared with isometric attempts (p < 0.05). The quadriceps activity decreased, and the gluteus maximus and shank muscle activity increased with increasing height (p ≤ 0.024). Moreover, the vastus muscles decreased only for the 1-RM trial while remaining stable at the same positions in the isometric trials (p = 0.04), indicating that potentiation occurs. Our findings suggest that a co-contraction between the hip and knee extensors, together with potentiation from the vastus muscles during ascent, creates a poor biomechanical region for force output, and thereby the sticking region among recreationally resistance trained males during 1-RM Smith machine squats.